Digital Media and EdTech-Based Instruction for Students and Teachers with Disabilities in Jordan - alzubi, ahmad (RADINKA JAYA UTAMA PUBLISHER, 2024)
There is a need for evaluations to help us understand the associations found in research on special education and new media. The researcher in this study explores the role of digital media in public education, with a specific emphasis on the role of digital media in the education of students with special needs and other types of disabilities. We used qualitative studies for our investigation. Under this pedagogical framework, it will provide helpful materials for digital media teachers and students who may not be fully aware of the benefits and significance of special education in the context of digital media instruction and education. Because there aren't enough studies on the subject, the sample size for this article is 12. The special edition on digital media and educational technology-based education for children with impairments. Initially, the selected pieces were dispersed in 2020 and 2022. Information required for the review's assessment was assembled by classifying the collected data according to the review's rubric. The review is the most useful tool for this assessment since it provides the best method for arranging both large amounts of data and personal judgments. In addition to describing how instructors and library media workers may work together to address the needs of children with disabilities, this article gives an overview of both physical and digital access to the library's resources. Research conducted by specialists has shown a positive correlation between all of these biomarkers.